Pengaruh Kombinasi Zat Pengatur Tumbuh terhadap Perkecambahan dan Inisiasi Tunas Kurma (Phoenix dactylifera L.) Kultivar Sukari - Nikmatullah, Aluh; Nufus, Novita Hidayatun (Bioscientist : Jurnal Ilmiah Biologi, 2021)
The study was conducted to determine the effect of several compositions of growth regulators (PGR) on germination and shoot initiation of dates (Phoenix dactylifera L.) in vitro. The study consisted of 2 experimental stages. The first phase of the study was aimed to determine the effect of the addition of Gibberellin PGR on the length of time the sprouts appeared, the number of explants that germinated, and the length of the sprouts produced. The second stage of the research was to determine the combination of PGR Indhol Acetic Acid (IAA) and Benzyl Amino Purine (BAP) which was able to initiate the emergence of shoots in the hypocotyl of dates. The study was designed using a completely randomized design (CRD). The first experiment consisted of 3 media treatments, namely: agar without additional ZPT (GA0); agar medium with 50 ppm GA (GA1); and agar medium with 100 ppm GA (GA2). Each media treatment consisted of 5 seeds and was repeated 3 times. The second stage of the experiment was designed in a completely randomized design with 5 media treatments, namely: P0 (MS medium without PGR); P1 (MS + 1 ppm IAA + 1 ppm BAP); P2 (MS + 2 ppm IAA + 1 ppm BAP); P3 (MS + 3 ppm IAA + 1 ppm BAP); P4 (MS + 1 ppm IAA + 2 ppm BAP); and P5 (MS + 1 ppm IAA + 3 ppm BAP). Each treatment consisted of 5 explants and repeated 3 times. Parameter observation data were analyzed by Analysis of Variance (ANOVA) and if significant results were obtained, continued with the Least Significant Difference (BNT) further test. The results of the first experimental data analysis showed that the treatment with 50 ppm GA3 significantly shortened the time of emergence of sprouts to 10 days and the number of explants that germinated on average was 4.5 explants. The results of observations and data analysis in the second experiment showed that the combination of IAA and BAP ZPT were significantly able to induce shoot formation on P4 and P5 media, which were 2.83 and 1.3 explants that formed shoots, respectively. Treatment with P4 was able to significantly increase the number of shoots produced by an average of 2.63 shoots per explant.